Dielectric response of BaTiO electronic states under AC fields via microsecond time-resolved X-ray absorption spectroscopy - Kato, S.; Nakajima, N.; Yasui, S.; Yasuhara, S.; Fu, D.; Adachi, J.; Nitani, H.; Takeichi, Y.; Anspoks, Andris (Elsevier, 2021)
For the first time, the dielectric response of a BaTiO thin film under an AC electric field is investigated using microsecond time-resolved X-ray absorption spectroscopy at the Ti K-edge in order to clarify correlated contributions of each constituent atom on the electronic states. Intensities of the pre-edge peak and shoulder structure just below the main edge increase with an increase in the amplitude of the applied electric field, whereas that of the main peak decreases in an opposite manner. Based on the multiple scattering theory, the increase and decrease of the and main peaks are simulated for different Ti off-center displacements. Our results indicate that these spectral features reflect the inter- and intra-atomic hybridization of Ti 3 with O 2 and Ti 4 respectively. In contrast, the shoulder structure is not affected by changes in the Ti off-center displacement but is susceptible to the effect of the corner site Ba ions. This is the first experimental verification of electronic contribution of Ba to polarization reversal.----/ / /---- This is open access article of S. Kato, N. Nakajima, S. Yasui, S. Yasuhara, D. Fu, J. Adachi, H. Nitani, Y. Takeichi, A. Anspoks, Dielectric response of BaTiO3 electronic states under AC fields via microsecond time-resolved X-ray absorption spectroscopy (DOI 10.1016/j.actamat.2021.116681), Acta Materialia, Volume 207, 2021,116681 - under the CC BY license (http://creativecommons.org/licenses/by/4.0/ )
This research was performed under the approval of the Photon Factory Program Advisory Committee (PF-PAC; Contract Numbers 2015G580, 2017G587, and 2019G614) and was ﬁnancially supported by JSPS KAKENHI Grant Numbers 18H01153 , 19H02426 , and 18K19126 . The experiment for measuring spectra in Fig. 6 (b) was performed on beamline BM26A (proposal MA 2731) at the European Synchrotron Radiation Facility (ESRF), Grenoble, France. We are grateful to Local Contact at the ESRF for providing assistance in using beamline BM26A. Institute of Solid State Physics, University of Latvia as the Center of Excellence has received funding from the European Union’s Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement No. 739508, project CAMART². © 2021 Acta Materialia Inc. Published by Elsevier Ltd. This is an open access article under the CC BY license (http://creativecommons.org/licenses/by/4.0/ )
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; Ferroelectricity; Electrical properties; Electronic structure; External electric field; X-ray absorption spectroscopy